(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Cholelithiasis (gallstone disease) is a prevalent gastrointestinal disorder influenced by cholesterol metabolism and biliary motility. Hypothyroidism, through mechanisms such as dyslipidemia, reduced bile flow, and altered sphincter of Oddi function, may contribute to gallstone formation. Despite previous studies, the association remains inconclusive. This study aims to evaluate the correlation between clinical and subclinical hypothyroidism and cholelithiasis in an Indian cohort. Materials and Methods: A prospective observational study was conducted from October 2025 to January 2026, and it was carried out at the Department of General Surgery, Mahatma Gandhi Medical College Hospital and Research Centre, Jaipur. Eighty adult patients with ultrasonographically confirmed gallstones were recruited. Exclusion criteria included choledocholithiasis and unwillingness to participate. All patients underwent thyroid function testing (TSH, T3, T4) and gallstone characterization. Statistical analysis included Chi-square tests for categorical data and ROC curve analysis for TSH as a predictive marker. Results: Among the 80 patients, 65% were female and 52.5% were aged 31–50 years. Thyroid dysfunction was present in 40% of patients 25% had subclinical and 15% had clinical hypothyroidism. Female gender and age >40 was significantly associated with hypothyroidism. Hypothyroid patients more frequently had multiple stones and cholesterol- type stones. A significant association between hypothyroidism and cholelithiasis was observed (p = 0.032). ROC analysis of TSH showed moderate predictive value (AUC = 0.72; sensitivity = 68%, specificity = 75%). Conclusion: This study demonstrates a significant association between hypothyroidism especially subclinical forms and gallstone disease, particularly in women over 40. Routine thyroid screening should be considered in gallstone patients to aid early detection and potentially reduce disease progression or recurrence.